Recidiva Neural em hanseníase multibacilar após 6 anos de tratamento - Teixeira, Leandra Oliveira; Silva, Carlos Maximiliano Gaspar Carvalho Heil; Akamatsu, Hélcio Takeshi; Barreto, Jaison Antônio; Soares, Cleverson Teixeira [UNESP] (FapUNIFESP (SciELO), 2012)
This article presents a case of relapse, with isolated neural manifestation, in a multibacillary patient previously treated with multidrug therapy for multibacillary leprosy (24 doses). The patient returned to the service six years after the end of treatment, with pain in hands and legs. He was investigated, and the serological monitoring showed an important increase in anti-phenolic glycolipid serum levels. A neural recurrence was suspected, since the patient had no new skin lesions. A new biopsy in the right ulnar nerve showed a bacilloscopy of 2 +, compatible with relapse. This is a literature review of the etiological, clinical, propedeutical and diagnostic aspects of this situation so poorly understood. © 2012 by Anais Brasileiros de Dermatologia.
Neural relapse in multibacillary leprosy 6 years after end of treatment
Keywords: Biopsy; Borderline; Combined modality therapy; Leprosy; Recurrence; Serology; Ulnar nerve; amitriptyline; chlorpromazine; phenolic glycolipid; prednisone; pregabalin; adult; analgesia; case report; diagnostic test; disease activity; hand pain; human; leg pain; male; multibacillary leprosy; myography; nerve biopsy; nerve degeneration; neuritis; neuropathy; relapse; treatment outcome; ulnar nerve; Adult; Humans; Leprosy, Multibacillary; Male; Ulnar Nerve